2015
DOI: 10.1016/j.healun.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and demographic factors associated with post–lung transplantation survival in individuals with cystic fibrosis

Abstract: After lung transplantation, 5-year survival in Canadians with CF is 67%, and 50% of patients live >10 years. Despite these impressive probabilities, age at transplant, pancreatic sufficiency and B cepacia infection remain important determinants of survival after lung transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 31 publications
3
76
1
2
Order By: Relevance
“…For instance, median survival post-lung transplant is longer in Canadian CF patients compared to published studies of US CF patients. (32) (33) Although the LAS has been associated with shorter waiting times and improved transplant survival(35), and the number of patients with CF listed for lung transplantation has increased since its implementation, the proportion who have received a transplant has decreased. (36) In addition, Merlo et al showed that CF patients transplanted since the LAS was implemented had a higher risk of death compared to CF patients transplanted in the pre-LAS period.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, median survival post-lung transplant is longer in Canadian CF patients compared to published studies of US CF patients. (32) (33) Although the LAS has been associated with shorter waiting times and improved transplant survival(35), and the number of patients with CF listed for lung transplantation has increased since its implementation, the proportion who have received a transplant has decreased. (36) In addition, Merlo et al showed that CF patients transplanted since the LAS was implemented had a higher risk of death compared to CF patients transplanted in the pre-LAS period.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies, including a recent study of Canadian patients with CF, have demonstrated that survival is significantly shortened in patients infected with B. cenocepacia who undergo LTx [1619]. Most LTx centers in the US consider B. cenocepacia to be an absolute contraindication to LTx.…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia cenocepacia (genomovar III) sputum culture positivity is a known marker of worse prognosis regardless of transplant status and is a contraindication to LTx at most centers. (1315) Other genomovars of Burkholderia cepacia complex have not been found to be associated with increased mortality and should not preclude referral for transplant evaluation. (16) The finding of a strong association between a positive Burkholderia cepacia complex culture and non-referral in our study highlights the possibility that some patients may be inappropriately denied referral, but this analysis does not provide further insight into this problem because genomovar subtypes were not available in the CFFPR until 2010.…”
Section: Discussionmentioning
confidence: 99%